A critical analysis of e-commerce contracts with relevance to the UAE and the United Kingdom. Issue 2 (12th March 2018) - Jaradt, Nashat Mahmoud
Abstract : Purpose: This paper aims to note how in-line the laws of each country are with the current best recommendations. The focus will be on the UAE and the UK for the purpose of creating a contrast between countries which have different regulations in general and between contrasting countries. Design/methodology/approach: This paper seeks to critically analyze the state of e-commerce contract laws in terms of what forms a part of the law normally and to what extent the similarities have been enacted in the international laws. A critical analysis of the information derived through the search was undertaken. This methodology was to ascertain the viability of the information in terms of its consistency with the contemporary laws in each country relating to e-commerce. Comparisons were made on topic-by-topic basis within the searches. Findings: It was clear through the information reviewed from both the UAE and the UK that both countries' laws are advanced in terms of being inclusive of the best common practices noted by the Organization for Economic Co-operation and Development (OECD). This shows that both countries, through their vastly different legal structures, have implemented similar laws with regard to e-commerce. Originality/value: This report is original in its value to e-commerce laws, as it is the first to consider how different countries e-commerce contract laws lineup to the OECD-recommended rules related to it. The value of this research is to show to what degree is there cohesion within the e-commerce laws on an international level.